Critical librarianship - Hines, Samantha Schmehl; Ketchum, David (Emerald Publishing Limited, 2020)
Librarianship has always had links with critical theory. As a public service, libraries cannot be separated from the society they exist in, and investigating the aspects of the culture they exist in is an important responsibility for all library and information professionals. In this exciting exploration of critical librarianship, expert authors from different walks of life investigate a variety of areas of librarianship in regards to critical theory. With chapters on feminist theory, sustainability and social justice, inclusivity, autism, and new motherhood, among others, this volume of Advances in Librarianship focuses on some of the most relevant issues of the 21st Century. With rigorous scholarship and diverse voices, Critical Librarianship is an unmissable volume of current research for all library and information professionals and researchers.
Includes index.
Keywords: Libraries and society.; Critical theory.; Language Arts & Disciplines -- Library & Information Science -- Administration & Management.; Community & outreach services.; elektronické knihy; electronic books